ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONVERSI LAHAN SAWAH DI KABUPATEN ACEH BESAR - Ari Aulia Tauficki; Raja Masbar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract Paddy fields in the Aceh Besar region in 2018 produced 155,420 tons of rice production in 2018 (Aceh Bulog). Compared with the previous production reduced due to the number of conversion of paddy fields. So, the authors conducted a study of the factors that influence the convertion of paddy fields in Aceh Besar district from 1998 to 2017. Based in the theoretical basis independent factors will be examined, namely the yield factor of total paddy production with the ratio of population to the length of the district road. The model used is multiple linear regression model with ordinary least square (OLS) method. The data used in the study are secondary data obtained from the Central Statistics Agency (BPS) and other relevant sources.Keywords: Conversion, Paddy Fields, Aceh Besar